Comparison of Different Variants of Intermediate Cluster Disinfection - Muriel Schulze; Franziska Nankemann; Anne Tellen; Julia Nitz; Yanchao Zhang; Stefanie Leimbach; Volker Krömker (Hygiene)
Intermediate cluster disinfection plays a vital role in preventing the transmission of mastitis pathogens during milking. This study evaluates the efficacy of different disinfection methods on teat liners through a randomized controlled field trial conducted on three dairy farms in Germany. The treatments assessed included dipping the liners in water, peracetic acid solution (PAS, 0.1%), and plasma-activated buffered solution (PABS). Total bacterial count (TBC) and the bacterial load of presumptive Staphylococcus (S.) aureus were measured using the wet–dry swab method. The results showed that PAS significantly reduced both TBC and S. aureus by 90% and 99%, respectively. PABS also demonstrated a significant reduction in the bacterial load of S. aureus. In contrast, dipping in water had no significant effect on either TBC or S. aureus bacterial counts. This study suggests that while PAS is the more effective disinfectant, PABS may offer an alternative with some antimicrobial activity. Further research on intermediate cluster disinfection in general is necessary to optimize its application and assess its long-term effectiveness in dairy farming practices.